Kebijakan Hukum Pidana Dalam Tindak Pidana Penyelundupan Barang Oleh Korporasi - Andi Purnomo (Publikasi Indonesia, 2022)
This study aims to determine the direction of criminal law formulation policy in the criminal act of smuggling goods by corporations according to Law Number 17 of 2006 concerning Amendments to Law Number 10 of 1995 concerning Customs and to determine the model of criminal liability in the criminal act of smuggling goods by corporations. The method of data collection that the author uses in preparing this thesis is by using library research. This library study the author collects data by reading, recording, studying and analyzing the contents of decisions related to the problem, including legislative literature, documents, archives and Supreme Court decision number 1734 K/Pid.Sus/2017, the Supreme Court of the Republic of Indonesia which decided that PT Tujuan Utama was a corporation that was found guilty in the crime of smuggling gold. The result of this study is that in the Supreme Court decision number 1734 K/Pid.Sus/2017 adheres to stricht liability, which is clearly not only individuals (company administrators) who can be held criminally liable, but the corporation / legal entity can also be subject to criminal liability. Of the seven models of criminal liability against corporations, only the vicarious liability and stricht liability models are explicitly adopted in the provisions of Law No. 17 of 2006 amending Law No. 10 of 1995 on Customs in handling criminal acts of smuggling goods by corporations. Meanwhile, other criminal liability models can be considered to be applied in handling criminal acts of smuggling by corporations in the future.